Planning Adolescent Mental Health Promotion Programming in Saskatoon. (August 2016) - Cushon, Jennifer; Waldner, Cheryl; Scott, Christina; Neudorf, Cordell
ABSTRACT: BACKGROUND: We assessed associations between key demographic risk factors and the outcome of depressed mood in Saskatoon, Saskatchewan, to inform the planning and implementation of mental health promotion programming in schools. METHODS: In the 2008/2009 school year, 3958 students from grades 5 through 8 from 76 elementary schools completed questions regarding depressed mood on the Student Health Survey administered by the Saskatoon Health Region. The demographic risk factors for depressed mood considered in this study included age, sex, cultural status, and neighborhood income, as well as the role of school and age cohorts or grades within schools. RESULTS: We found Aboriginal students were significantly more likely to report moderate/severe depressed mood than other students. We also found older female adolescents were significantly more likely to report moderate/severe depressed mood. Neighborhood income explained the largest proportion (40%) of depressed mood differences between schools. CONCLUSIONS: These results can inform the planning and implementation of mental health promotion programming by the health sector in Saskatoon's elementary schools, including an appropriate balance between targeted and population‐based interventions that address both the distal and proximal determinants of depressed mood in adolescents.